Flow training, flow states, and performance in elite athletes - Norsworthy, C.; Thelwel, R.; Weston, N.; Jackson, S. A. (International Journal of Sport Psychology, 2018)
Using a single-subject multiple-baseline design, the study examined the efficacy of a flow training program on flow states and performance of four elite level rock-climbers. Having received the intervention that comprised education, goal-setting, self-talk, and mindfulness stages, flow intensity, as measured by the Flow State Scale (FFS-2) increased. In addition, objective performance (time) and selfrated scores improved with, at least, medium effect sizes. Social validation indicated that participants found the training to be rewarding, and in line with the study findings. Such results propose further empirical research on flow training on elite athletes be undertaken to assess the intensity of flow experiences and performance scores. Future research examining retention data and education only interventions are advised. Implications arising from the present data are discussed.